A rare find - Lowell, Joanna (Berkley Romance, 2025)
"When an aspiring archaeologist teams up with her childhood enemy for a treasure hunt, they find it impossible to bury their growing feelings, in a charming queer historical romance from the author of A Shore Thing. Elfreda Marsden has finally made a major discovery--an ancient amulet proving the Viking army camped on her family's estate. Too bad her nemesis is back from London, freshly exiled after a scandal and ready to wreak havoc on her life. Georgie Redmayne is everything Elfreda isn't--charming, popular, carefree, distractingly attractive, and bored to death by the countryside. When the two collide (literally), the amulet is lost, and with it, Elfreda's big chance to lead a proper excavation. Now Elfreda needs new evidence of medieval activity, and Georgie needs money to escape the doldrums of Derbyshire. Joining forces to locate a hidden hoard of Viking gold is the best chance for them both. Marsdens and Redmaynes don't get along, and that's the least of the reasons these enemies can't dream of something more. But as the quest takes them on unexpected adventures, sparks of attraction ignite a feeling increasingly difficult to identify as hatred. It's far too risky to explore. And far too tempting to resist. Elfreda and Georgie soon find that the real treasure comes with a steep price... and the promise of a happiness beyond all measure"--